A scoping review on the barriers to and facilitators of health services utilisation related to refugee settlement in regional or rural areas of the host country - J. V. F. Coumans; S. Wark (BMC, 2024)
Abstract Background Healthcare access and equity are human rights. Worldwide conflicts, violence, and persecution have increased the number of people from refugee or refugee-like backgrounds. Because urban areas are already densely populated, governments have aimed to increase refugee resettlement in rural and/or regional areas. Because of the complex healthcare needs of refugees, this creates challenges for healthcare service providers. Identifying barriers to accessing healthcare in rural areas is therefore important to better inform policy settings and programmes that will provide culturally appropriate patient-centred care to the refugee community. Methods This review scoped 22 papers written in English between 2018 and July 2023 from five countries (Australia, New Zealand, Germany, Bangladesh, and Lebanon) in order to provide an overview of the barriers and possible solutions to facilitate refugees' access to healthcare. Results The reviewed literature summarised the perceptions of at least 3,561 different refugees and 259 rural health service providers and/or administrators and identified major challenges. These include communication (illiteracy in the resettlement country language and lack of a suitable interpreter), lack of cultural awareness of health services, discrimination, and access difficulties (transportation, availability of health specialist services, cost). As a consequence, it was identified that improving access to affordable housing, employment through credential recognition, competence-level education for children, facilitating language training, and adapting health information would increase resettlement and encourage access to healthcare. Conclusions Refugees face significant barriers to accessing and engaging with healthcare services. This impacts their integration into rural communities and increases the prevalence of psychosocial issues like feelings of loneliness, low self-esteem, a lack of autonomy, and a lack of empowerment over informed decision-making, especially for women, jobless men, and the elderly. These findings support the need for additional support for refugees and healthcare providers to improve language proficiency and cultural competency. Policymakers need to improve the availability and accessibility of employment, housing accessibility, and service mobility. Additionally, more research is needed to assess the efficacy of emerging innovative programmes that aim to close the gap by delivering culturally appropriate patient-centred care to refugee communities in rural areas.